Construction of Intelligent Information Service System for Small and Medium-Sized Manufacturing Enterprises - Yingshi Kang; Zijun Zheng (Dianxin kexue)
The characteristics of the small and medium-sized manufacturing enterprises information system in China were analyzed. Combined with the“cloud manufacture”technology and service concept, an intelligence information service based on cloud model was introduced. The overall system architecture of manufacturing resources layer, the network layer, the virtual service layer, the core service layer and the wisdom application layer were put forward. Also the virtual service mechanism and service delivery methods were explained.